Power Relations in Perpustakaan Ajaib Bibbi Bokken by Jostein Gaarder and Klaus Hagerup - Nokiamy Sesena Tamba (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
Young Adult (YA) literature is a relatively new genre in Indonesia. However, the development of YA literature in USA demonstrates that this popular genre is not merely entertaining but also possesses aesthetic value and the potential to address relevant sociocultural issues. One notable work reflecting the development of YA literature is Bibbi Bokken's Magic Library by Jostein Gaarder and Klaus Hagerup which was translated into Indonesian in 2016. The story is set in the world of libraries and not only entertains but also raises power dynamics through the interactions between two cousins, namely Nils and Berit. Therefore, this study aims to illustrate how power relations are depicted in the story and how the characters respond when confronted with these power relations. As the results, there are three types of power relations in the book using Michel Foucault's theory: power relations over discourse, thought, and discipline through literary culture.